THE URGENCY OF CRIMINALIZING SURROGATE MOTHER PRACTICES REVIEWED FROM INDONESIAN CRIMINAL LAW - Prija Djatmika; Setiawan Noerdajasakti; Putri Carera Santi Romauli Simamora (CV. RADJA PUBLIKA, 2025)
The advancement of science goes hand in hand with the development of increasingly varied community needs, requiring the law to continue to be dynamic in order to keep pace with these developments. So that with the advancement of technology and the development of science in the health sector, it is hoped that it can help support the welfare and health of mankind. But in this case, the question arises whether Indonesian law has accommodated technological advances in the health sector, especially in terms of the implementation of surrogate mothers. In Indonesia, the regulation regarding the inability of surrogate mothers is still not explicitly regulated in the law so that it still seems vague, both in terms of its regulation and in terms of its sanctions. Using a normative legal research method, this study analyzes whether according to Indonesian positive law, the practice of surrogate mother can be criminalized.